Petrosaviaceae, A new family record for India - Bhat, Nazir Ahmad; Jeri, Licha; Roy, Dilip Kr.; Kumar, Yogendra (Bangladesh Journal of Plant Taxonomy, 2018)
Not available. Bangladesh J. Plant Taxon. 25(1): 113-117, 2018 (June)